Building citizenship in the university: A proposal for coexistence and conflict resolution skills - Chávez Ponce, Daniel Fernando (Universidad de Sonora, 2021)
Higher Education Institutes are committed to offer a well-rounded education for the student body, so it´s not possible to refer to a quality education if the citizenship skills are not contemplated. These are grouped into three areas: coexistence and peace, participation and democratic responsibility and plurality, identity and valuation of differences. Since conflict is unavoidable in the interaction of individuals, it’s relevant to develop emotional skills that allow them to be resolved peacefully. For this reason, this paper presents a proposal to promote civic competences through coexistence and peace, teaching conflict resolution skills by collaboration. The proposal was structured in a constructivist approach, having as a method collaborative learning, from which derives creative, meaningful and integrative didactic strategies. It's objective is the development of skills to solve conflicts collaboratively, managing emotions, improving interpersonal relationships and assuming the leadership role without authoritarianism, a fundamental aspect for student performance and their future role in society. Keywords: Education Citizenship, coexistence, resolution skills, university students